External oxidant-compatible phosphorus(III)-directed site-selective C–H carbonylation - Dong, Ben (Sci Adv, 2020)
The first development of an external oxidant-compatible system involving a phosphorus(III)-directed C–H functionalization has been uncovered. An efficient C–H esterification of indoles with CO and alcohols has been reported in which the high reactivity and the exclusive C7-selectivity derives from the selection of a P(III)–directing group and the utilization of benzoquinone as an external oxidant with palladium catalysis. This strategy shows many advantages, involving an easily accessible and removable directing group, the use of cheap carbonylation sources, a broad substrate scope, and excellent positional selectivity. Two cyclopalladated intermediates were confirmed by x-ray analysis, uncovering key mechanistic features of this P(III)-directed C–H metalation event.